GAMBARAN TINGKAT PENGETAHUAN IBU POSTPARUM TENTANG BABY BLUES DI BPM LISMARINI - Melia Rahma; Ririn Anggraini; Yuningsih Yuningsih (STIKes Al-Insyirah Pekanbaru, 2023)
The incidence of Baby Blues Syndrome or Postpartum Blues in Asia itself is quite high and varies between 26 - 85%.whereas in Indonesia the incidence of baby blues or postpartum blues is between 50-70% of postpartum women.This study aims to describe the knowledge of postpartum mothers about the baby blues. This study used a descriptive survey method with samples taken by accidental sampling. The results of the univariate analysis were based on the respondents' knowledge of the definition of baby blues, namely that of 92 respondents the majority of respondents had a good level of knowledge, namely 55 respondents (92.4%). And for knowledge about the causes of baby blues most of the respondents have a sufficient level of knowledge, namely 65 respondents (70.7%).For knowledge about the symptoms of baby blues, most of the respondents had a good level of knowledge, namely 75 respondents (81.5%).And respondents who have a sufficient level of knowledge for the impact of the baby blues are 64 respondents (69.9%). Meanwhile, in the management of baby blues, respondents who had less knowledge were 79 respondents (85.9%).